Biochemical evidence linking the GIX thymocyte surface antigen to the gp69/71 envelope glycoprotein of murine leukemia virus (The Rockefeller University Press, 1975)
It is known that the thymocyte surface antigen GIX is found in some strains of mice and not others, and that its expression in mice of strain 129, in which most extensive genetic studies have been made, is controlled by two unlinked cellular chromosomal loci. We have now isolated a protein with a mol wt of approximately 70,000 daltons from the surface of thymocytes from 129 mice, which have antigenic and biochemical properties characteristic of the gp69/71 envelope component of murine leukemia virus. Our evidence is compatible with the conclusion that it carries the GIX antigen.